Infants' Understanding of Preferences When Agents Make Inconsistent Choices. (26th May 2017) - Luo, Yuyan; Hennefield, Laura; Mou, Yi; vanMarle, Kristy; Markson, Lori
Abstract : This study showed that 8.5‐month‐old infants seemed to consider the consistency of an agent's choices in attributing preferences to her. When the agent consistently chose one object over another, three or four times consecutively, infants acted as if they had interpreted her actions as evidence for her preference. In contrast, when the agent inconsistently chose between the two objects, at the ratio of 1:3, infants did not seem to interpret her actions as suggesting her preference. Converging evidence was obtained from infants' responses across a looking‐time task and an action task. The results are discussed in terms of how infants might use frequencies of agents' actions directed toward different objects to understand agents' preferences.